The first fossil spider (Araneae: Palpimanoidea) from the Lower Jurassic (Grimmen, Germany) - Selden, Paul A.; Dunlop, Jason A. (Zootaxa, 2014)
The first Lower Jurassic (Lias) spider is described as Seppo koponeni n. gen. & n. sp. from a single female specimen from Grimmen, Germany. It most likely belongs to the Palpimanoidea, on account of the presence of cheliceral peg teeth and other features consistent with palpimanoid families, though its familial placement is uncertain. Its presence in the region at that time concurs with ideas about the more widespread presence of palpimanoids across the world in the early Mesozoic, before the break-up of Pangaea.